2019
DOI: 10.1016/j.jhin.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of influenza point-of-care testing and patient cohorting during a high-incidence season: a retrospective analysis of impact on infection prevention and control and clinical outcomes

Abstract: Implementation of influenza point-of-care-testing and patient-cohorting during a high-incidence season: a retrospective analysis of impact on infection prevention and control and clinical outcomes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 18 publications
(23 reference statements)
1
41
1
Order By: Relevance
“…It has been shown that the potential benefit to patients and the healthcare systems that they present to may be considerable. The study by Youngs et al suggests reduced number of hospital-acquired laboratory-confirmed influenza cases per day (0.66 cases vs 0.95 cases), a shorter median length of stay (5.5 days vs 7.5 days) and increased antiviral prescribing (80% vs 64.1%) [4]. In addition to this, the authors note that by cohorting the influenza-positive patients, trusts were able to collectively release 779 single rooms for use with other patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been shown that the potential benefit to patients and the healthcare systems that they present to may be considerable. The study by Youngs et al suggests reduced number of hospital-acquired laboratory-confirmed influenza cases per day (0.66 cases vs 0.95 cases), a shorter median length of stay (5.5 days vs 7.5 days) and increased antiviral prescribing (80% vs 64.1%) [4]. In addition to this, the authors note that by cohorting the influenza-positive patients, trusts were able to collectively release 779 single rooms for use with other patients.…”
Section: Discussionmentioning
confidence: 98%
“…The most obvious opportunity for the use of POCTs would be for more rapid triaging of patients at the hospital front door, putting them into appropriate care pathways thereby reducing the risk of onward transmission and consequent burden within hospitals and on the health service. Once at hospital, POCTs enable patient cohorting in bays of general wards or on designated influenza wards with reduced consequent risk of nosocomial transmission of influenza and improved patient flow [4]. On a larger scale, this could become the normal pathway associated with this group of patients in which POCTs may be cost saving by avoiding nosocomial hospital infections and ensuring appropriate targeted prescribing of antivirals/antibiotics.…”
Section: Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper evaluates the realworld performance of Liat. The impact of Liat on infection prevention and control and clinical outcomes is discussed in an accompanying paper [8].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The numerous nosocomial outbreaks described in hospital rooms, adult and neonatal intensive care units, transplant centers, and other chronic care centers increase the frequency of influenza cases related to health care to 15%. 10 Being the most frequent immunopreventable disease in developed countries, the main strategy for the prevention and control of influenza is vaccination, in a common effort of public health authorities, health professionals, and patients. 1 Sufficient evidence supports the vaccination of health professionals as one of the most important measures in the reduction of nosocomial transmission of influenza virus.…”
Section: Introductionmentioning
confidence: 99%